MRI from picture to proton - McRobbie, Donald W., 1958-; Moore, Elizabeth A.; Graves, Martin J (Cambridge : Cambridge University Press, 2017)
MR is a powerful modality. At its most advanced, it can be used not just to image anatomy and pathology, but to investigate organ function, to probe in vivo chemistry, and even to visualise the brain thinking. However, clinicians, technologists and scientists struggle with the study of the subject. The result is sometimes an obscurity of understanding, or a dilution of scientific truth, resulting in misconceptions. This is why MRI from Picture to Proton has achieved its reputation for practical clarity. MR is introduced as a tool, with coverage starting from the images, equipment and scanning protocols and traced back towards the underlying physics theory. With new content on quantitative MRI, MR safety, multi-band excitation, Dixon imaging, MR elastography and advanced pulse sequences, and with additional supportive materials available on the book's website, this new edition is completely revised and updated to reflect the best use of modern MR technology. [Ed.].
[Contents] 1. MR: what's the attraction?. -- Part A. The Basic Stuff. -- 2. Early daze: your first week in MR. -- 3. Seeing is believing: introduction to image contrast. -- 4. Lost in the pulse sequence jungle?. -- 5. The devil's in the detail: pixels, matrices and slices. -- 6. What you set is what you get: basic image optimization. -- 7. Improving your image: how to avoid artefacts. -- 8. Spaced out: spatial encoding. -- 9. Getting in tune: resonance and relaxation. -- 10. Let's talk technical: MR equipment. -- 11. Ghosts in the machine: quality control. -- Part B. The Specialist Stuff. -- 12. Acronyms anonymous I: spin echo. -- 13. Acronyms anonymous II: gradient echo. -- 14. The parallel universe: parallel imaging and novel acquisition techniques. -- 15. Go with the flow: MR angiography. -- 16. A heart-to-heart discussion: cardiac MRI. -- 17. It's not just squiggles: in vivo spectroscopy. -- 18. To BOLDly go: fMRI, perfusion and diffusion. -- 19. Making it count: quantitative MRI. -- 20. But is it safe? Bio-effects. -- 21. Where are we going now?